Strategic design of magnetic carbonaceous nanocomposites and its application as multifunctional adsorbent. (May 2020) - Vieira, Laís Helena Sousa; Sganzerla Sabino, Carla Manuela; Soares Júnior, Francisco Holanda; Rocha, Janaina Sobreira; Castro, Manuela Oliveira; Alencar, Rafael Silva; Souza da Costa, Luelc; Viana, Bartolomeu Cruz; Jardim de Paula, Amauri; Soares, João Maria; Gomes Souza Filho, Antônio; Otubo, Larissa; et al.
Abstract: Magnetic carbonaceous nanocomposites (MCN) were prepared by hydrothermal carbonization (HTC) of a carbohydrate in the presence of Fe 3+, followed by thermal treatment with KOH for simultaneous activation and magnetization. The precursor formed (IOCN) in the HTC process contained iron oxide nanoparticles encapsulated in the hydrochar matrix. The thermochemical parameters of the activation (temperature and IOCN/KOH mass-ratio) were varied to achieve an increase of the specific surface area along with formation of magnetic phases in MCN compared to IOCN. Activation temperature was found to be responsible for the structural and morphological properties of the MCNs whereas the IOCN/KOH mass-ratio controlled the porosity. The magnetic properties of the MCNs originated from the formation of Fe3 O4 and Fe 0 phases, which are encapsulated in the carbonaceous material. The MCNs were tested for adsorption of methylene blue (MB) dye, followed by magnetic separation. The MCN, produced in the optimized conditions, showed a specific surface area of 766 m 2  g −1, magnetization of 8 emu g −1 and a MB adsorption capacity of 570 mg g −1 . Detailed kinetic and isotherm studies of MB adsorption were also performed. The methodology of simultaneous activation and magnetization to generate MCNs, presented here, could be extended to obtain new multifunctional carbon-based nanocomposite adsorbent starting from different biomasses. Graphical abstract: Image 1